THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS: PROBLEMS IN EVALUATING STUDENT LEARNING OUTCOMES IN JUNIOR HIGH SCHOOLS - Saraya, Ana; Mardhatillah, Annisa; Fitriani, Elisa Novianur; Adiyono, Adiyono (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
This research is related to issues in the evaluation of student learning outcomes that have not been explored in the aspects of Islamic religious education. The papers scrutinize the role of Islamic religious education teachers in the context of junior secondary schools and the impact of the problems faced by them on the evaluation of student learning outcomes. Through literature review and analysis of secondary data with a case study approach, this research presents a comprehensive picture of the challenges and important role of Islamic religious education teachers in improving students' understanding of Islam and the application of religious values in their daily lives. This study aims to determine the role of Islamic Education teachers in evaluating Islamic Religious Education learning outcomes at SMPN 11 Sungai Tuak Village Tanah Grogot. The study employed qualitative research. Research data were obtained from interviews with PAI teachers at SMPN 11 Sungai Tuak Village Tanah Grogot. Interviews were conducted to obtain information about the role of PAI teachers in evaluating student learning outcomes. The results showed that the type of evaluation applied by PAI teachers, media/tools used in evaluating, PAI activities in the school, methods in evaluating, problems in evaluating, and supporting factors, inhibiting factors and solutions to these problems.